Spatial Analysis of Multiple Sclerosis Disease in Tehran Metropolitan Zone, Iran, 2001-2012. - Mahbubeh Saei; Kourosh Holakouie-Naieni; Ehsan Mostafavi; Mohammad Ali Sahraian; Mahmood Mahmoodi; Mohammad Ali Mansournia; Ali Hosseini (Tehran University of Medical Sciences, 2014)
Multiple Sclerosis (MS) is a disease with high disabling disorders and considerable social and economic impacts. This study was conducted to analyze the spatial distribution of MS disease in Tehran, Iran during 2001-2012.The existing information in the MS patients' medical files who had registered in Iranian MS Society (IMSS), located in Tehran office, was used for analysis. The relationship between diseases incidences in 22 zones of Tehran based on estimated socio-economic status (SES) of each zone was evaluated. High and low clustering approach was used in order to investigate the disease's distribution pattern meanwhile, Getis Ord's Gi test and Hot Spot analysis approach has been used to detect high risk zones of the disease.A total of 6027 MS patients were registered between 2001- 2012 which 4580 (%75.99) were women. During the study period, zone number 6 figured as the most high risk zone for the disease (P